2022
DOI: 10.1002/jha2.384
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of duodenal‐type follicular lymphoma: A single‐center retrospective study

Abstract: Duodenal‐type follicular lymphoma (FL) is a rare and newly recognized disease. Few data are available on the outcomes and treatment strategies for patients with duodenal‐type FL. We aimed to investigate the clinical features and outcomes of duodenal‐type FL. We defined duodenal‐type FL as involvement of the duodenum, without nodal or extranodal lesions other than intestinal lesions, pathologically diagnosed as FL. We reviewed 26 patients with duodenal‐type FL between January 2011 and December 2020 at Kobe City… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…However, the remaining patients presented with multifocal lesions involving the terminal ileum and duodenum. This finding is in agreement with recent data demonstrating that patients with DFL frequently have multiple lesions in the distal portion of the duodenum or other regions of the small intestine in addition to the second portion of the duodenum (20)(21)(22)(23). We assumed the possibility that in at least some patients with DFL, extraduodenal lesions might not be detected because of the lack of enteroscopic examination.…”
Section: Discussionsupporting
confidence: 92%
“…However, the remaining patients presented with multifocal lesions involving the terminal ileum and duodenum. This finding is in agreement with recent data demonstrating that patients with DFL frequently have multiple lesions in the distal portion of the duodenum or other regions of the small intestine in addition to the second portion of the duodenum (20)(21)(22)(23). We assumed the possibility that in at least some patients with DFL, extraduodenal lesions might not be detected because of the lack of enteroscopic examination.…”
Section: Discussionsupporting
confidence: 92%
“…Among the available treatment approaches for DFL, the wait-and-watch approach does not require the administration of immediate treatment. However, as mentioned earlier, there is a possibility of high-grade transformation necessitating continuous follow-up examinations [7,11]. Consequently, routine surveillance tests such as routine endoscopy, VCE, CT, and FDG-PET/CT are essential.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic findings are most frequently described as nodular polyps or mass-like lesions but have also been described as white granular or polypoid lesions observed in a pattern similar to lymphomatous polyposis. 2,6,[10][11][12][13][14] There are no established comorbidities or risk factors associated with GI-FL. However, location of the polyps within the GI tract appears to be an important factor associated with OS.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have found DFL to be indolent with no clear difference in outcomes, including OS regardless of treatment approach. 4 , 7 , 10 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%